The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America - Ferreira, Marina Izabel Grave; Ferreira, Rodrigo Lopes; Gil-Santana, Hélcio R. (Zootaxa, 2016)
A survey on species of the genus Zelurus Hahn, 1826 (Reduviidae) occurring in Brazilian caves is provided. Zelurus tambejua sp. n. and Zelurus gerevatinga sp. n. collected from caves in Brazil are described. Comments about the current and potential distribution of the genus as a whole and of species of Zelurus found in caves for South America are also provided.